Biomaterial-assisted tumor therapy: A brief review of hydroxyapatite nanoparticles and its composites used in bone tumors therapy - Zhang, Quan; Qiang, Lei; Liu, Yihao; Fan, Minjie; Si, Xinxin; Zheng, Pengfei (Frontiers in Bioengineering and Biotechnology, 2023)
Malignant bone tumors can inflict significant damage to affected bones, leaving patients to contend with issues like residual tumor cells, bone defects, and bacterial infections post-surgery. However, hydroxyapatite nanoparticles (nHAp), the principal inorganic constituent of natural bone, possess numerous advantages such as high biocompatibility, bone conduction ability, and a large surface area. Moreover, nHAp's nanoscale particle size enables it to impede the growth of various tumor cells via diverse pathways. This article presents a comprehensive review of relevant literature spanning the past two decades concerning nHAp and bone tumors. The primary goal is to explore the mechanisms responsible for nHAp's ability to hinder tumor initiation and progression, as well as to investigate the potential of integrating other drugs and components for bone tumor diagnosis and treatment. Lastly, the article discusses future prospects for the development of hydroxyapatite materials as a promising modality for tumor therapy.